Role of non-coding RNAs in radiosensitivity of colorectal cancer: A narrative review - Huang, Chun-Ming; Tsai, Hsiang-Lin; Chen, Yen-Cheng; Huang, Ching-Wen; Li, Ching-Chun; Su, Wei-Chih; Chang, Tsung-Kun; Yeh, Yung-Sung; Chen, Po-Jung; Huang, Ming-Yii; Wang, Jaw-Yuan (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is a global public health concern because of its high prevalence and mortality. Although radiotherapy is a key method for treating CRC, radioresistance is an obstacle to radiotherapy use. The molecular mechanisms underlying the radioresistance of CRC remain unclear. Recently, increasing evidence has revealed the multiple regulatory functions of non-coding RNAs (ncRNAs) in numerous malignancies, including CRC. Several ncRNAs have been reported to be involved in the determination of radiosensitivity of CRC cells, and some have excellent potential to be prognostic biomarkers or therapeutic targets in CRC treatment. The present review discusses the biological functions and underlying mechanisms of ncRNAs (primarily lncRNA, miRNA, and circRNA) in the regulation of the radiosensitivity of CRC. We also evaluate studies that examined ncRNAs as biomarkers of response to radiation and as therapeutic targets for enhancing radiosensitivity.